If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5k + 6) = 102 Reorder the terms: -3(6 + 5k) = 102 (6 * -3 + 5k * -3) = 102 (-18 + -15k) = 102 Solving -18 + -15k = 102 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -15k = 102 + 18 Combine like terms: -18 + 18 = 0 0 + -15k = 102 + 18 -15k = 102 + 18 Combine like terms: 102 + 18 = 120 -15k = 120 Divide each side by '-15'. k = -8 Simplifying k = -8
| 4(c+5)=8 | | 7x^2+31x+-20=0 | | k/3=9 | | 4lnx+28ln=20 | | 7(3-5r)=126 | | 6(6+5m)=186 | | 4ln(x+7)=20 | | 7+2n/2=10 | | -3+11=-2z+3(z-2) | | -2A+8A-18+5A=-A+14-5A+2 | | 4x^2-16x+80=113 | | 2x+8=4x+11 | | 5x^2-11x-2=0 | | 16x-4y=32 | | 6(2a+7)=102 | | 10x^2-11x-2=0 | | 98b^2=2 | | (6r-3)(8r-3)= | | x-7=2x-3 | | 13+3x-9=10x-14-5x | | -9=108 | | 3x^2-3=45 | | x^2-24x+1=0 | | 100(x-3)=450-50 | | t/3-2=9 | | -6(8+6k)=-228 | | 7/5(40) | | x+7/5x=96 | | 6d/4=24 | | -153-12x=71+2x | | -5+7=5x-4(x-1) | | 9Y-1=y-5 |